Primary cN0 lip squamous cell carcinoma and elective neck dissection: Systematic review and meta-analysis - Bhandari, Kishor; Wang, Dian-can; Li, Shan-chang; Jiang, Bing-hua; Guo, Yu-xing; Koirala, Ujjwal; Du, Xiao-yan (Head & neck, 2015)
Background Management of clinically negative lymph nodes (cN0) in primary lip squamous cell carcinoma (SCC) has always been a controversial topic. Methods A systematic review of English–language electronic databases using Medline, Embase, Cochrane library, Google Scholar, SCI, and specific journals on the subject matter was done. Only the studies mentioning primary nonmetastatic lip SCC with cN0 neck treated by surgery only and having at least 2 years of follow‐up data were selected. The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement for reporting systematic reviews and meta‐analysis was followed. Results The pooled estimate of occult metastasis in neck dissected specimen was 0.17 (95% confidence interval [CI], 0.10–0.28) and that of delayed nodal metastasis in patients without neck dissection was 0.08 (95% CI, 0.01–0.18). Conclusion The results do not prove sufficient to justify elective treatment of the neck in primary cN0 lip SCC and close observation would be a viable option in such cases. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1392–1400, 2015